Growth and differentiation factors and their orthodontic implications: A scoping review - Crystal Runa Soans; M.S. Ravi; Monisha P Chelery; Sujata Shirodkar; Prachi Pundir; Shradha S. Parsekar (MethodsX)
Background: Growth and differentiation factors (GDFs) are a class of biological mediators that play an important role to stimulate and regulate the wound healing process. Some of the GDFs are known to play a role in orthodontics. Objectives: To map the evidence related to GDFs in orthodontics and to identify the role of GDFs in craniofacial morphogenesis, periodontal remodeling and orthodontic tooth movement. Methods: We have planned a scoping review to achieve the objectives. Search will be conducted in various databases to identify English language publications. Additionally, we will search the first ten pages of Google Scholar and the reference lists of included studies. This review will include all animal or human studies exploring preventive, interceptive and corrective treatments in orthodontics. Two reviewers will independently screen titles and abstracts and full-texts and extract the data of included studies. Disagreement will be resolved by discussion. The results will be presented in a descriptive format using diagrams and tables. Ethics and dissemination: The current study does not require ethical approval. Results of review findings will be disseminated through a peer-reviewed publication or conference presentation. Registration: The protocol is registered with the Open Science Framework.